Study on the Genetic Diversity Characteristics of the Endemic Plant Rhododendron bailiense in Guizhou, China Based on SNP Molecular Markers - Jun Luo; Congjun Yuan; Haodong Wang; Jianhua Zhang; Jin Chen; Shuang He; Meng Chen; Xiaoyong Dai; Dali Luo (Ecology and Evolution, 2025)
ABSTRACT Rhododendron bailiense was identified as a new species in 2013, with approximately 150 individuals existing globally, found only in Dafang County and Panzhou City, Guizhou Province, China. Despite its discovery, the genetic diversity and population structure of this species remain poorly understood, hindering efforts to collect and conserve wild germplasm resources. In this study, double digest restriction‐site associated DNA sequencing was conducted on 26 samples from two populations of R. bailiense to identify single nucleotide polymorphism (SNP) loci. Using these data, the research explores the genetic diversity and structure of R. bailiense populations and infers their population dynamics and evolutionary history. The results indicate that R. bailiense has a moderate level of genetic diversity (π = 0.2489, Ho = 0.2039, He = 0.2331). Genetic differentiation between populations is relatively high (55.94%), with a genetic differentiation coefficient (FST) of 0.1907. This suggests that R. bailiense historically might have been a large population, which, due to geological historical events, became fragmented into the two existing populations. The Panzhou population demonstrates a heterozygote selection advantage. Conversely, the Dafang population faces the risk of inbreeding depression, further exacerbated by its limited gene flow. Consequently, in situ conservation is recommended for the Panzhou population, while ex‐situ conservation is suggested for the Dafang population. Additionally, research on breeding techniques is necessary to expand the population size while maintaining high genetic diversity.